Describing Fermi acceleration with a scaling approach: The Bouncer model revisited - Leonel, Edson Denis [UNESP]; Livorati, Andre L. P. [UNESP] (Elsevier B.V., 2008)
The behavior of average velocities on a dissipative version of the classical bouncer model is described using scaling arguments. The description of the model is made by use of a two-dimensional nonlinear area contracting map. Our results reveal that the model experiences a transition from limited to unlimited energy growth as the dissipation vanishes. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: suppression of Fermi acceleration